2008
DOI: 10.1167/iovs.07-1621
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age and Fixation Instability on Retinotopic Mapping of Primary Visual Cortex

Abstract: Although the cortical area remains unchanged, healthy older persons show less BOLD activity in V1 than do younger persons. Normal variations in fixation stability do not have a significant effect on the accuracy of experiments to determine the retinotopic structure of the visual cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
35
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 34 publications
8
35
3
Order By: Relevance
“…6). These findings differ from those of other studies which found no significant differences in fixation stability were found between young and old observers when fixating a target presented on a uniform background (Crossland et al, 2008;Kosnik, Fikre, & Sekuler, 1986). In our study, observers experienced perceptual rivalry and reported the dominant percept.…”
Section: Control Testscontrasting
confidence: 99%
“…6). These findings differ from those of other studies which found no significant differences in fixation stability were found between young and old observers when fixating a target presented on a uniform background (Crossland et al, 2008;Kosnik, Fikre, & Sekuler, 1986). In our study, observers experienced perceptual rivalry and reported the dominant percept.…”
Section: Control Testscontrasting
confidence: 99%
“…As in the individual age groups, significant main effects of visual status (F = 23.40, p < 10 -5 ) and ROI (F = 60.00, p < 10 -15 ) were found, as well as a significant interaction between them (F = 7.18, p < 0.01). There was also a main effect of age (F = 8.82, p < 0.01), a feature we have noted previously 27 . However, there were no significant interactions between age and visual status (F = 2.09, p = 0.15) or age and ROI (F = 2.31, p = 0.11).…”
Section: Group Effectssupporting
confidence: 76%
“…The intersubject variability in the patient group may also be due to a combination of factors such age, lesion size, and acuity, as well as differences in cognitive strategies. 51 Even among control subjects who achieve very similar performance levels in each paradigm, and are of similar age and acuities (as in the case of control subjects 101 and 102), the activation patterns analyzed across the lobes of the brain show differences that suggest different networking strategies for processing visual tasks.…”
Section: Intersubject Reproducibilitymentioning
confidence: 99%